2021
DOI: 10.1098/rspb.2020.2906
|View full text |Cite
|
Sign up to set email alerts
|

Long-term noise pollution affects seedling recruitment and community composition, with negative effects persisting after removal

Abstract: Noise pollution can affect species' behaviours and distributions and may hold significant consequences for natural communities. While several studies have researched short-term effects of noise, no long-term research has examined whether observed patterns persist or if community recovery can occur. We used a long-term study system in New Mexico to examine the effects of continuous natural gas well noise exposure on seedling recruitment of foundational tree species ( Pinus edulis , … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…Bird response to gas-well-compressor noise was found species-specific with some key seed dispersers (mountain bluebirds and Woodhouse’s scrub-jays) avoiding noisy areas where pollinators like hummingbirds had on the contrary higher reproductive success [14]. Long-term consequences include alterations in plant communities that persist after removal of the noise source [15]. The propensity of anthropogenic noise to indirectly affect species, and typically primary producers, through a series of nested direct interactions had also been suggested experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…Bird response to gas-well-compressor noise was found species-specific with some key seed dispersers (mountain bluebirds and Woodhouse’s scrub-jays) avoiding noisy areas where pollinators like hummingbirds had on the contrary higher reproductive success [14]. Long-term consequences include alterations in plant communities that persist after removal of the noise source [15]. The propensity of anthropogenic noise to indirectly affect species, and typically primary producers, through a series of nested direct interactions had also been suggested experimentally.…”
Section: Introductionmentioning
confidence: 99%
“…However, researchers working in grassland prairies documented an effect of the gas extraction infrastructure, rather than the noise that was associated with it (Nenninger and Koper, 2018), showing the complexity of the mechanisms underlying this disturbance. The physiological costs of noise have also been documented using this natural study system demonstrating impacts to glucocorticoid-signaling and reduced fitness across bird species (Kleist et al, 2018), while truly long-term cascading impacts of noise exposure were recently found in a study that revealed chronic noise exposure (15 years) impacted seedling recruitment and woody plant community structure (Phillips et al, 2021). These effects were still in evidence 2-4 years after the removal of noise.…”
Section: State Of the Knowledge About Chronic Noise Effects On Commun...mentioning
confidence: 61%
“…There is mixed evidence from terrestrial systems on ecological recovery in quieter conditions (e.g. birdsong in lockdown increased 28 , 29 , while seed dispersal around disused gas wells did not 30 ) but, in general, reproductive success and survival are strongly linked to population stability 31 . In fish in particular, improvements in energy intake and energy expenditure could be important drivers of population growth via size-dependent fecundity 32 .…”
Section: Discussionmentioning
confidence: 99%